Perioperative challenges and anesthetic management in Thoraco-Omphalopagus twin separation: A case report - R Safdhar Hasmi; Sateesh Verma; Vinita Singh; Gyanendra Pratap Singh (Saudi Journal of Anaesthesia)
Administering anesthesia for the separation of conjoined twins poses distinct challenges for anesthesiologists. The rarity of these surgeries, coupled with the unique anatomical variations in each case, makes every separation procedure a distinct experience. This case report details the anesthetic management and the challenges faced during the separation of thoraco-omphalopagus twins at our tertiary care hospital.